How innovators reframe resources in the strategy-making process to gain innovation adoption - Kannan-Narasimhan, Rangapriya (Priya); Lawrence, Barbara S. (Strategic Management Journal, 2018)
[Research summary: This multicompany qualitative field study combines strategy process and strategy-as-practice perspectives to show how innovators successfully gain adoption for their autonomous innovations by reframing the meaning and potential of the associated internal resources to create fit with their organization's strategy. Mapping the five steps involved in the resource reframing process onto the different parts of the Bower-Burgelman process model of strategic change shows that innovators can shape the strategic context for their autonomous innovations before external market validation is available. These findings confirm the unique potential and importance of different forms of discourse in shaping the strategic innovation process. Managerial summary: How do innovators from lower levels of an organization gain approval for their innovations especially when their ideas do not readily fit their organization's strategy? To explore this question, we conducted 138 interviews with innovators and their decision makers in 14 firms based in Silicon Valley. We find that successful innovators shape a story supporting their innovation by rethinking their firm's current and potential resources. They then use this story to convince decision makers that their innovation creates unique competitive advantage. Contrary to conventional wisdom, decision makers approved such innovations even without external validation, solely based on the innovators' success in depicting their reorganization of the firm's resources.]